ONE QUALITY concept: a narrative perspective to unravel nutritional challenges, controversies, and the imperative need of transforming our food systems - Menta, Roberto; Rosso, Ginevra; Canzoneri, Federico (Frontiers in Nutrition, 2024)
Ensuring a healthy and sustainable diet for all should be a global priority, and to achieve this goal the food system requires substantial changes. Adopting a one-size-fits-all approach is not feasible, and we need to consider the cultural particularities of each geography and not try to export models that work in one place but may be unsustainable in others. Our discussion will center on two key aspects within this overarching process: a) the combination of a rigorous evidence-based approach with existing or proposed Nutritional Guidelines and policies required to realize the "ONE HEALTH" and "ONE QUALITY" concepts. Examining the Mediterranean diet and the latest findings on saturated fats will aid us in comprehending the necessary paradigm shift required to formulate new guidelines with substantial impact in preventing the rising prevalence of Non-Communicable Diseases worldwide; b) the adequacy and scope of the data bank necessary to develop a global, science-based approach.